TECHNIQUE FOR RESECTION OF ATHEROSCLEROTIC ABDOMINAL AORTIC ANEURYSM WITH ANOMALOUS ORIGIN OF RENAL ARTERIES AND PELVIC DYSTOPIA OF THE LEFT KIDNEY - A. E. Zotikov; S. S. Ilyin; V. A. Kulbak; D. I. Maryan; B. Sh. Gogiya (Атеротромбоз)
This article describes the clinical observation of a patient with an atherosclerotic abdominal aortic aneurysm and pelvic dystopia of the left kidney. Due to the anomalous origin of renal arteries, we have chosen a method of treatment consisted of resection and an aortic prosthetics and reimplantation of vessels extending from the aortic aneurysm. 5 years after surgery, the patient had an aneurysm of the left iliac artery, which required repeated intervention. Our approach allowed us to preserve all the renal arteries and renal function.